1
$\begingroup$

I am unable to recover the limit of this function.

$$ \lim_{x \to +\infty} \left (\frac{1}{\sqrt{x}} \times \sqrt[3]{x+1} \right ) $$

I have tried many ways of solving it. These are the two simplest:

  • Variable substitution

Using $y = \sqrt[3]{x+1} $, with which I got a common factor $\sqrt{y-1}$ and got

$$ \lim_{x \to +\infty} \left (\frac{1}{\sqrt{y^3-1}} \times y \right) = \lim_{x \to +\infty} \left (\frac{\sqrt{y^2}}{\sqrt{y^3-1}} \right) = \lim_{x \to +\infty} \left (\frac{\sqrt{y^2}}{\sqrt{y^3(1-\frac{1}{y^3})}} \right) = \lim_{x \to +\infty} \left (\frac{1}{\sqrt{y \left (1-\frac{1}{y^3} \right)}} \right) = \frac{1}{+\infty \times 1} = 0 $$

  • Using the common factor $\sqrt{x}$

$\sqrt[3]{x+1} = \sqrt[6]{(x+1)^2} = \sqrt[6]{x^2+2x+1} = \sqrt[6]{x^3 (\frac{1}{x}+\frac{2}{x^2}+\frac{1}{x^3})}=\sqrt{x} \left (\sqrt[6]{\frac{1}{x}+\frac{2}{x^2}+\frac{1}{x^3}} \right )$

and therefore I got

$$ \lim_{x \to +\infty} \left (\frac{\sqrt{x} \left (\sqrt[6]{\frac{1}{x}+\frac{2}{x^2}+\frac{1}{x^3}} \right )}{\sqrt{x}} \right ) = \lim_{x \to +\infty} \left (\sqrt[6]{\frac{1}{x}+\frac{2}{x^2}+\frac{1}{x^3}} \right ) = \sqrt[6]{\frac{1}{+\infty}+\frac{1}{+\infty}+\frac{1}{+\infty}} = 0 $$

However, I found that the limit is positive when I plotted a function with this expression. I have plotted it here, you can look at it yourselves. This means my calculations are wrong. What am I doing wrong and how do I solve it correcly? Thank you for the help.

$\endgroup$
  • $\begingroup$ The link does not work $\endgroup$ – vrugtehagel Apr 23 '17 at 21:08
  • $\begingroup$ $ \lim_{x \to +\infty} \left (\frac{1}{\sqrt{x}} \times \sqrt[3]{x+1} \right )= \lim_{x \to +\infty} \left (\frac{1}{\sqrt[6]{x^3}} \times \sqrt[6]{(x+1)^2} \right )= \sqrt[6]{ \lim_{x \to +\infty} \left (\frac{{(x+1)^2} }{{x^3}} \right ) }=0 $ $\endgroup$ – N74 Apr 23 '17 at 22:04
2
$\begingroup$

Your calculations are right! $$ \begin{aligned} \lim _{x\to \infty }\left(\frac{\sqrt[3]{1+x}}{\sqrt{x}}\right) & = \lim _{t\to 0\:}\left(\frac{\sqrt[3]{1+\frac{1}{t}}}{\sqrt{\frac{1}{t}}}\right) \\& = \lim _{t\to 0\:}\left(\sqrt[6]{t}\sqrt[3]{t+1}\right) \\& =0^{\frac{1}{6}}\sqrt[3]{0+1} = \color{red}{0} \end{aligned} $$

enter image description here

$\endgroup$
  • $\begingroup$ Thank you very much for posting the plot as well! I had checked the link and I could not find any better way of posting it. If you could tell me how I can do this as you did and save you the work for the future, I would really appreciate further. And as you see, if the limit is zero as I also think, it goes to zero very, very slowly. Also, I had seen a book stating the limit was some $ \frac{\sqrt{2}}{a} $ being this $a$ a number I don't remember. When I checked the plot I have also seen this odd plateauing so I got concerned. $\endgroup$ – BrunoCAfonso Apr 23 '17 at 23:37
  • $\begingroup$ I used desmos.com and then i saved the pic of the screen and crop it $\endgroup$ – Amarildo Apr 24 '17 at 7:54
0
$\begingroup$

Multiplying and dividing by $x^{1/3}$ we get $\frac{1}{\sqrt{x}}(x+1)^{1/3}=\frac{x^{1/3}}{\sqrt{x}}(\frac{x+1}{x})^{1/3}$. The factor $(\frac{x+1}{x})^{1/3}$ tends to $1$ as $x \to \infty$. The factor $\frac{x^{1/3}}{\sqrt{x}}$ equals $x^{-1/6}$ that tends to $0$ as $x \to \infty$. So the limit you're looking for is $0$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.